Do Local Forecasters Have Better Information? - Benhima, Kenza; Bolliger, Elio (The Review of Economics and Statistics, 2025)
Abstract Using inflation and growth forecasts for a panel of emerging and advanced economies, we provide evidence that foreign forecasters publish and update their forecasts less frequently than local forecasters and make larger errors. We provide tests that identify differences in information frictions across groups and show that the lower accuracy of foreigners is not due to more irrational expectations, but to less precise information. This informational advantage is linked both to barriers to information and to incentives and is typically stronger when uncertainty is lower. These results provide a basis for disciplining international finance and trade models with heterogeneous information.